2019
DOI: 10.3390/ani9090638
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha Hypothesis: Did Lateralized Cattle–Human Interactions Change the Script for Western Culture?

Abstract: Simple SummaryThe domestication of cattle was a key innovation early in the development of Western civilization. Cattle provided the main tractor force to enable broad-scale agriculture and the land transportation of goods. Their initial significance was religiously celebrated as the bull-like creator god ’El, in Canaan (modern day Lebanon and Syria), and for over 6000 years in Ancient Egypt as the sky-goddess Hathor, often depicted as a sacred cow. In addition, the Ancient Egyptian hieroglyphic logogram of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Due to this decussation, the left side of the brain receives visual input from the right visual field of eyes, while the right side receives feedback from the left visual field. Given the eye position in cattle, the majority (80%-87%) of visual pathways are contralateral (projecting to the opposite side) (Robins, 2019). Studies have demonstrated interhemispheric transmission from short-term to long-term memory processing.…”
Section: Vision Capability In Cattle and The Behaviour Related To Vis...mentioning
confidence: 99%
“…Due to this decussation, the left side of the brain receives visual input from the right visual field of eyes, while the right side receives feedback from the left visual field. Given the eye position in cattle, the majority (80%-87%) of visual pathways are contralateral (projecting to the opposite side) (Robins, 2019). Studies have demonstrated interhemispheric transmission from short-term to long-term memory processing.…”
Section: Vision Capability In Cattle and The Behaviour Related To Vis...mentioning
confidence: 99%